2019
DOI: 10.1177/1524838019869098
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Forgiveness, Bullying, and Cyberbullying in Adolescence: A Systematic Review

Abstract: The study of bullying in adolescence has received increased attention over the past several decades. A growing body of research highlights the role of forgiveness and its association with aggression. In this article, we systematically review published studies on the association among online and traditional bullying and forgiveness in adolescents. Systematic searches were conducted in PsycINFO, MEDLINE, PsycArticles, and Scopus databases. From a total of 1,093 studies, 637 were nonduplicated studies and 18 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 59 publications
5
35
0
9
Order By: Relevance
“…This understanding of forgiveness would serve to protect victims of aggression from further unhealthy relationships, even when aggressions continues in schools, boosting courage to report the bullying aggressions. Finally, interventions may benefit from parental and teacher components to broaden the scope of the intervention, such as actively involving parents and teachers to improve forgiveness in adolescents instead of calling for revenge or avoidance [ 32 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This understanding of forgiveness would serve to protect victims of aggression from further unhealthy relationships, even when aggressions continues in schools, boosting courage to report the bullying aggressions. Finally, interventions may benefit from parental and teacher components to broaden the scope of the intervention, such as actively involving parents and teachers to improve forgiveness in adolescents instead of calling for revenge or avoidance [ 32 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…One individual approach to dealing with negative emotions after interpersonal transgressions that has been found to have related to less emotional hurt in response to past different instances of aggression is forgiveness [ 29 , 30 ]. Although there is a growing body of research focusing on forgiveness and bullying, the majority of studies have been conducted in the context of adulthood [ 31 , 32 ]. Consequently, this study focuses on forgiveness as one potentially important individual protective factor to effectively contribute to the scarce existing literature.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have analyzed the phenomenon in adolescence (DeSmet et al, 2015;Ho et al, 2017;Extremera et al, 2018;Quintana et al, 2019), however, lately, high prevalence rates have also been found in the university environment. So, researchers have suggested that prevalence rates of students who are victimized by electronic means during the higher education period may range from 5 to 40% (Finn, 2004;Lindsay and Krysik, 2012;Faucher et al, 2014;Zalaquett and Chatters, 2014).…”
Section: Introductionmentioning
confidence: 99%